전북지역 일부 청소년의 아침식사대용 쌀 기반 가정간편식 인식 및 선호도 - 오해림(Hae-Rim Oh); 김현숙(Hyunsuk Kim); 정수진(Su-Jin Jung); 차연수(Youn-Soo Cha) (Journal of nutrition and health, 2021)
Purpose: Although, the rate of skipping breakfast among adolescents has increased in recent years, there has been an increase in the consumption of home meal replacement (HMR). This study examines the recognition and preference of rice-based Korean style HMR for breakfast among adolescents in located at Jeollabuk-do. Methods: Total of 550 middle- and high-school students of Jeollabuk-do enrolled in this study signing a consent of participation. After conducting a preliminary survey, the questionnaire employed was modified according to the purpose of this study, and the self-recording method was appliedto fill out the questionnaire. Data were analyzed using IBM SPSS Statistics 25. The 2-test was performed for categorical variables, whereas continuous variables were analyzed by the independent t-test. Results: Results of this study determined that 272 students (54.6%) belonged tobreakfasteating group and 226 (45.4%) were in the breakfast-skipping group. The reasons specified by both groups for eating HMR were 'convenient to cook', 'delicious', and 'time-saving'. The a result of analyzing perception of the importance of HMR by classifying as whether to eat or not to eat breakfast, revealed that compared to the breakfast-skipping group, the breakfast-eating group considered 'hygiene and cleanliness' as important factors (p < 0.001). Considering the gender, school, and breakfast consumption, the most preferred Korean HMR were 'triangular gimbap', 'gimbap', and 'rice balls'. Conclusion: Results of this study indicate, when considering adolescents, there is a necessary for continuous researches to develop convenient breakfast substitutes that are easily consumed. Moreover, we believe that it is essential to impart proper cooking education and recipe distribution of the menu. 본 연구는 전라북도 일부 지역 중·고등학생을 대상으로 아침식사대용 쌀 기반 HMR 인식과 그 선호도를 조사하였으며, 요약하면 다음과 같다. 조사대상자의 아침식사 결식 여부 행태는 아침식사군 (주 4회 이상 섭취군)이 272명 (54.6%), 아침결식군 (주 3회 이하 섭취군)이 226명(45.4%)으로 조사되었다. 조사대상자의 HMR 섭취 만족도는 고등학생 (48.2%)이 중학생(39.1%)과 비교 시 유의적으로 HMR 만족도가 높았으며, 여학생이 남학생 보다 HMR 만족도가 높았다. 조사대상자의 아침식사 대용식의 필요성조사 결과는 남학생이 여학생보다 유의적으로 높은 비율로 응답하였다 (p < 0.01). 아침식사 대용식으로써 쌀 기반의 한식 식사 패턴의 선호도는 아침식사자가 58.9%로 아침결식자보다 높고, 고등학생이 중학생보다 유의적으로 높은 것으로 나타났다 (p < 0.01). 또한 조사대상자의 아침식사대용으로 쌀 기반 HMR 선호 식품은 '삼각김밥', '주먹밥', '김밥' 순으로 나타났다. 따라서 청소년들의 아침결식의 큰 이유인 '시간이 없어서'와 '입맛이 없어서'를 고려하여 손쉽게 섭취할 수 있는 아침식사대용 간편식 메뉴 개발 연구는 지속적으로 이루어져야 하고, 해당 메뉴의 조리교육 및 레시피 보급이 필요할 것으로 사료된다.